Research Trends on Flipped Classroom: A Bibliometric Analysis (2012–2023) - Maria Goreti Patmi Yulita (Journal of Computers for Science and Mathematics Learning, 2024)
Technology is developing very fast especially during the pandemic of COVID-19. The objectives of this paper are to analyze the current dynamics of the flipped classroom studies and offer a direction for further research on the topic. The Scopus database yielded a total of 3206 papers that were published in journals until September 2023. Search volume for “flipped classroom” rose over time and peaked in 2022, according to the data. The field was founded in 2012, as evidenced by the publication of the first paper. The most cited article was written by O’Flaherty J. and Phillips C. The most prolific writer is Hew, KF. In a flipped classroom, the most common topics are engineering, computer science, and social sciences. BMC Medical Education, Education Sciences, Education And Information Technologies are the most productive sources. Harvard Medical School, The University of Hong Kong, The Education University of Hong Kong are the most active institutions. United States, China and Spain are the most relevant countries. Trending keywords include “flipped classroom,” “human,” “humans,” “teaching,” and “education.” An extensive summary of the field’s research output and potential future prospects is given in this review.